The education of the Indian in Natal,(1860-1947). Volume One - Cooppan,Somarsundarum (Department of Philosophy, 2023)
The educational development 0f a people 1s influenced by various factors - political, economic and social. The growth of Indian education in Natal must be studied in this context.